The cleft team social worker. (20th April 2016) - Kaye, Alison; Lybrand, Sandra
ABSTRACT: The birth of a child with significant medical problems poses challenges for most families. Congenital orofacial clefting is a common condition affecting families worldwide. Orofacial clefting requires long-term medical care and can affect multiple body systems. Having a child with a chronic medical condition such as cleft lip or palate creates many psychosocial ramifications for a family. This article describes the importance of medical social work involvement in the coordinated care for children with cleft lip and palate. Specific cases spanning prenatal care through adolescence are used to highlight the variety of complex psychosocial situations encountered in the multidisciplinary cleft team setting.